برنامج إرشادي مقترح لخفض الضغط النفسي للمراهق من اسرة مفككة (المطلق) قائم على نظرية (أرون باك) - علال, اكرام (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة باللغة العربية: العنوان: برنامج إرشادي مقترح لخفض الضغط النفسي للمراهق من أسرة مفككة (المطلق) قائم على نظرية (أرون باك). هدفت الدراسة الى بناء برنامج إرشادي فردي على مراهق من أسرة مفككة (ابن المطلق) بمؤسسات التربوية (ثانويات، متوسطات) بولاية الوادي بالجزائر ومحاولة الخفض من مستوى الضغط النفسي لديهم. حيث يستند هذا البرنامج إلى بناء تقنيات وأساليب الإرشاد المعرفي العلاجي لنظرية أرون باك، ومحاولة الكشف عن مدى استمرارية أثر البرنامج بعد انتهاء جلساته، من خلال تطبيقه على عينة أبناء المطلقين. وقد استخدمت في هذه الدراسة المنهج الوصفي والتحليلي في الجانب الميداني حيث تم تصميم أداة بحث وبرنامج إرشادي. والأداة تتمثل في مقياس الضغط النفسي (شبكة الملاحظة) الموجهة إلى (المعلمين والمراقبين والأولياء)، بينما إحتوى البرنامج الإرشادي على (08) جلسات إرشادية وتكونت عينة الدراسة من (10) تلاميذ (أبناء الطلقين) تم إختبارهم بطريقة قصدية لغرض الدراسة وهو تخفيض من الضغط النفسي أما عينة التجربة فقد تكونت من (04) تلاميذ أثر عليهم الطلاق بدرجة كبيرة حيث تبين لديهم الضغط النفسي بشكل واضح تتراوح أعمارهم ما بين (16 - 20 سنة). وقد جرى التحقق من صلاحية المقياس المستخدم قبل التطبيق النهائي للبرنامج. كما أظهرت الدراسة أنه يمكن ترشيد الضغط النفسي من خلال برنامج إرشادي قائم على نظرية أرون باك. ملخص الدراسة باللغة الانجليزية: The study aimed to build an individual counseling program for a teenager from a divorced family (A child of divorce) in educational institutions (secondary schools, intermediate schools) in El ued, Algeria, and try to reduce their psychological stress level. This program is based on the construction of techniques and methods of therapeutic cognitive counseling according to Aaron Buck's theory, and an attempt to reveal the extent of the continuity of the program's impact after the end of its sessions, by applying it to a sample of children of divorce. In this study, the descriptive and analytical approach was used in the field, where a research tool and an extension program were designed. Where a research tool and an indicative program were designed. The tool is a psychological stress scale (observation network) directed to (teachers, observers, and parents), while the counseling program contained (08) counseling sessions, and the study sample consisted of (10) students (children of divorce) who were deliberately tested for the study, which is a reduction of psychological pressure. As for the experimental sample, it consisted of (04) Pupils who were greatly affected by divorce, as they clearly showed psychological pressure, their ages ranged between (16-20 years). The validity of the scale used has been verified before the final application of the program. The study also showed that psychological pressure can be rationalized through a counseling program based on Aaron Buck's theory.
تخصص علم نفس